PENGARUH KEPEMIMPINAN SEBAGAI LEADER DALAM SUATU ORGANISASI - Erwin Syahputra (Nusantara Hasana Berdikari, 2022)
Research on leadership has existed since World War II, but there are still differences of opinion. These differences of opinion can be due to each of them having different teachings. Likewise, there are differences between leadership and management. The study of leadership began in the time of Aristotle, while management began in the 20th century with the birth of industrial society. The research method used is descriptive analysis method, namely by describing in general the facts found, then analyzed based on the theories put forward by experts that are related to the problems to be studied. While the data collection techniques carried out by the author in this study can be done by means of library research and field studies. Ideal leadership is a dream or hope for every organization. There are 8 (eight) ideal leadership characters, namely: intelligent, responsible, honest, trustworthy, initiative, consistent, firm and straightforward. Character is a key determinant in the success of an organization. This will bring blessings to all members of the organization in it. Forward and backward, the success and failure of an organization is largely determined by the leader, because the leader is the controller and determines the direction that the organization wants to take towards the goals to be achieved.